Material Study Of Linear Low-Density Polyethylene (Lldpe) For The Application Of Geotube Structurer - Zailani, Zurlaika; Abdullah, Muhammad A'imullah (Progress in Engineering Application and Technology, 2023)
My Flexitank Industries Sdn Bhd (MYF) is proposing a new Geotube material composed of Linear Low-density Polyethylene (LLDPE) to be tested for its suitability as a non-dewatering Geotube substitute for the conventional dewatering method. The goal of the study is to determine if LLDPE is suitable to increase the Geotube's durability by testing its tensile strength and water permeability. The research will use the Universal Tensile Machine and the ASTM D882 standard to evaluate mechanical properties, and will create a LLDPE bag with a tubular shape by double-sealing the edges of the LLDPE sheet to imitate the Geotube structure and withstand wave impact along the shoreline. Throughout this research, the yield strength, and the stress at maximum load value of the sealed LLDPE sheet portrayed a great value in which can conclude that the sealed LLDPE sheets can be use as the non-dewatering Geotube structurer. The research will focus on testing the seal's tensile strength and water permeability properties to improve MYF Industries' future operations.